The Use of Bio-Inks and the Era of Bioengineering and Tooth Regeneration - Saman Tauqir; Saqib Ali; Anand Marya (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Objective: To review existing literature and provide an update on the current use of Bio-Inks and potential future use. Material and Methods: A MeSH keyword search was conducted to find out relevant articles for this short review. Results: Bio inks used in 3D printing grafting require various properties essential for the selection. Combining multiple methods and improved properties is essential for developing successful bio-inks for 3D grafting of functional tissues and tooth pulp regeneration from stem cells. To date, researchers have made many efforts to grow teeth based on stem cells and inculcate regeneration of teeth along with surrounding tissues like alveolar bones and periodontal ligaments. Conclusion: 3D printing with Bio-Inks requires strict adherence to safety protocols for successful outcomes, making it difficult to employ this routinely.